31 Outcomes of access site in patients with stemi. (30th September 2020) - Ranganathan, D; Howley, R; O'Connor, P; Kearney, P
Abstract : Introduction: Current ESC Guidelines (2017) recommends radial access over femoral access (Class 1A ) during primary PCI for STEMI. However, radial access can be technically more challenging, particularly in older patients, smaller patients and females in whom the radial artery may be small and brachiaand brachocephalic tortuously is frequently encountered. This may delay re-perfusion, and increase radiation exposure. Aim: We aimed to analyse real-world clinical data on the choice of access site with success of intervention, complications rate and radiation exposure in patients presenting with STEMI. Methods: We retrospectively evaluated 227 patients presenting to Cork University Hospital between January 2019 to December 2019 with a ST-elevation myocardial infarction. 58 patients were excluded due to lack of sufficient data and the remaining 169 patients were compared based on their access site. Observed variables included success of intervention, all-cause mortality, complication rate and radiation exposure. Outcomes of patients operated via the radial approach versus the femoral approach was compared using Chi-Square. We used SPSS for all statistical analysis and p-values of <0.05 was considered to be statistically significant. Results: The demographics of the 169 patients analysed are described (table 1 ). 120 patients (71%) had a radial artery for access of which 7 patients transitioned to an alternative access site (5 patients to right femoral artery and 2 patients to left radial artery). Of the 49 patients in femoral access site, 6 patients had no palpable right radial pulse/Barbeau's test negative, 5 were anticipated to require intra-aortic balloon pump/temporary wire insertion and 1 had flexure contracture of right arm from previous stroke. Of 5 patients in the left radial access, 2 had previous CABG, 2 had no palpable right radial pulse and 1 had AV fistula involving right forearm. Fourteen patients were thrombolysed at another centre, 1 brought for immediate PPCI despite successful lysis and 13 required rescue PCI. There were 3 unsuccessful cases between the 2 groups (p-valve 0.283). The patients with graft study in each group had successful interventions regardless of access site. When comparing radiation exposure, there was no significant difference between radial and femoral access on fluoroscopy timing and dose area product (p-value 0.2425). There was a higher average creatinine rise associated with femoral access, possibly a consequence of higher contrast volume. In regard to complications, there was higher mortality risk associated with femoral access (p-value 0.038) and complication rates (p-value 0.048) and significant overall adverse outcomes (p-value 0.005986) compared to radial access. Conclusion: Complication rates were very low, but our study findings support previous studies, such as MATRIX, RIFLE-STEACS and RIVAL, with regard to lower vascular complications associated with radial access. The study revealed similar radiation exposure levels between the 2 access sites.